2020
DOI: 10.1111/apt.15707
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a digital medicine programme on hepatitis C treatment adherence and efficacy in adults at high risk for non‐adherence

Abstract: Background: Direct-acting anti-virals (DAA) are highly effective for hepatitis C virus (HCV) treatment, but perceived risks of medication non-adherence may restrict access to care. Digital medicine programme (DMP) has improved adherence and outcomes for some conditions. Aims: To conduct a prospective, single-arm, open-label study across the United States to assess the impact of DMP on adherence and efficacy in adults with chronic HCV infection at high risk for non-adherence. Methods: Eligible participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Of the 18 clinical trials that reported on the deployment of a DPS in human subjects, most were single-arm pilot studies ( n = 16). 22 , 24 30 , 32 , 34 39 , 43 Two were cluster-randomized pilot clinical trials among individuals with uncontrolled hypertension and diabetes. 31 , 33 All 18 investigations deployed the DPS with a primary endpoint of demonstrating the feasibility of their use in select patient populations where medication adherence is important.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 18 clinical trials that reported on the deployment of a DPS in human subjects, most were single-arm pilot studies ( n = 16). 22 , 24 30 , 32 , 34 39 , 43 Two were cluster-randomized pilot clinical trials among individuals with uncontrolled hypertension and diabetes. 31 , 33 All 18 investigations deployed the DPS with a primary endpoint of demonstrating the feasibility of their use in select patient populations where medication adherence is important.…”
Section: Resultsmentioning
confidence: 99%
“…While most of the pilot studies reviewed sought to define the feasibility of using a DPS in an indicated disease state, four focused on biological outcomes. 31 , 34 , 37 , 43 Two pilot investigations were conducted among individuals with hepatitis C, who used the DPS with either ledipasvir/sofosbuvir or glecaprevir/pibrentasvir or fosbuvir/velpatasvir. In the first study, all participants had preexisting risk factors for medication non-adherence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations